Assessment of pulpal changes in periodontitis patients using CBCT: a volumetric analysis - Almarghlani, Ammar; Alsahafi, Reem A.; Alqahtani, Fatimah K.; Alnowailaty, Yousef; Barayan, Mohammed; Aladwani, Ameerah; Bokhari, Amr (Frontiers in Dental Medicine, 2025)
IntroductionEvidence suggests that periodontal disease can lead to inflammation and degeneration within dental pulp, highlighting the need for dental professionals to understand this association better.ObjectiveThe objective for this study was to establish a correlation between pulp volume and periodontal disease using Cone-Beam Computed Tomography (CBCT) imaging.MethodsA cross-sectional study design was employed for the collected data from 148 patients aged 39.51 years using dental images obtained by CBCT and analyzed by medical software to create three-dimensional (3D) images. Pulp-volume analysis was performed using Amira software and measurements were derived using bio-models generated from CBCT images. Obtained data was analyzed using SPSS-27 statistical software.ResultsThe mean pulp volume between healthy and teeth with periodontitis showed certain differences. The mean low and largest pulp volumes of 9.15 ± 3.3 mm3 and 15.24 ± 4.2 mm3 were observed involving teeth # 41 and teeth # 13, respectively. Furthermore, a higher mean of pulp volume was observed in healthy teeth than in periodontitis-diagnosed teeth except for teeth # 33 and 43. The significant difference (p < 0.05) was easily detected involving teeth # 22, 23, 11, and 13. However, the lowest difference, with non-significant difference (p > 0.05), involving teeth # 43, 31, and 33 was observed.DiscussionThe study's findings underscore a significant correlation between periodontitis and reduced pulp volume, suggesting that periodontal inflammation may influence pupal remodeling.